Ortalis remota: a forgotten and critically endangered species of chachalaca (Galliformes: Cracidae) from Eastern Brazil - Silveira, Luís Fábio; Tomotani, Barbara Mizumo; Cestari, César; Straube, Fernando C.; Piacentini, Vitor De Q. (Zootaxa, 2017)
The habits and general behaviour of the chachalacas (Ortalis spp.) in the Neotropics are well known. However, the validity and even the diagnoses of some taxa are poorly studied, and this may jeopardize the conservation of some populations. Within Ortalis guttata two subspecies are currently accepted, the nominate O. g. guttata (Spix) and O. g. subaffinis Todd. A third taxa, O. g. remota Pinto, 1960, was described based on a single specimen from SE Mato Grosso do Sul state, Brazil. Despite appreciable differences between O. g. remota and other members of Ortalis, this taxon was considered as a synonym of O. squamata, a species restricted to the lowlands of Atlantic Forest, east of Serra do Mar. Here we performed coloration and geographical distribution analysis of O. g. remota with additional examination of the holotype and a thorough comparison of skins and photos with other members of Ortalis (O. squamata, O. araucuan, and O. guttata) intending to disentangle the above taxonomic puzzle. Our results showed that a newly recognized population of O. g. remota differs consistently from all other Ortalis taxa currently treated as distinct species in plumage characters and geographic distribution. Therefore, we defend that it should be considered a valid species, Ortalis remota Pinto, 1960. Ortalis remota has a very restricted range on the upper Paraná River and it is threatened by deforestation and construction of dams.